PERSEPSI KONSUMEN TERHADAP BAURAN PEMASARAN DI KLAPPERPIE KOTA PEKANBARU - Arie Shandy; Shorea Khaswarina; Evy Maharani (PEKBIS, 2017)
Marketing is a total system of business activities that designed to plan, price,promotion and distribution of goods to satisfy the desires and reach the targetmarket. This study aimed to know consumer perception on marketing mix inKlapperPie store. Survey method was used in this study and purposive samplingwas used to get 50 costumers of KlapperPie store as samples. This study took placein KlapperPie store. Analyze descriptively was used on this study. The resultsshowed that consumer perception on marketing mix from variables of product, price,place and promotion then service, consumer gave a mark with good categorized dueto variable of product has an interesting color and fresh fruit as the topping, flavor ofproduct, package, quality of fruit freshness, quality of hygiene product, and displayquality of product with the average score of 3,75 on good categorized. Indicators onprice variable were affordable price, suitability price with quality products,competitive price, and price affected on purchasing power with the average score of3,71 on good categorized. Indicators on place variable were (public transportation,visibility, parking facility and business location) with the score of 3,39 on quite goodcategorized. Promotion variable with the indicators of mouth to mouth promotion andsocial media promotion with the average score of 3,03 on quite good categorized.The last variable was service variable with indicators of bargaining product service,purchasing product service, handover product service, and delivery product with theaverage score of 3,61 on good categorized.